The Role of Mental Health and Sustainable Learning Behavior of Students in Education Sector Influences Sustainable Environment - Gu, Zhaoliang; Li, Pu; Zhang, Aiai; Xu, Xiaoqiang; Gu, Fengmiao (Frontiers in Psychology, 2022)
Mental health has been declared as the essential component of overall human well-being however there has been a very steep rate of depression and anxiety in the students that exhibit their social and personal burden. It has been widely accepted that the well being and mental health of the individuals is the mix of psychological, genetic, social, life style factors and the environmental exposure. Due to pandemic, the shift in the class room learning to e-learning has also been disturbed by the mental health of students; which consequently affects the environmental stability. The current study has also measured the effect of mental health on the e-learning behavior (psychological motivation, peer collaboration, cognitive problem solving, interaction with instructor, community support and learning management). The population of the study was the undergraduate students enrolled in the colleges of China and were chosen via convenient sampling. The findings of the study show that mental health has a significant positive effect on the e-learning behavior of the students and it consequently affects the environmental sustainability. The educational institutions are improving their e-learning programs conducted by understanding the preferences and the challenges of the students regarding online learning, educational institutes should make the policies regarding online education and teaching methodologies. Further, the current study has taken the undergraduate students as the sample, in future studies, these relationships can be checked in higher education as well.